2020
DOI: 10.7759/cureus.11602
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic and Vagal Responses Elicited by Acute Stress in Rats

Abstract: Introduction Acute emotional stress triggers autonomic responses that affect sympathovagal balance. However, the temporal pattern of changes in each autonomic arm during stress and recovery remains unclear. Therefore, we analyzed separately sympathetic and vagal activity, elicited by acute unpredictable stress in a rat model. Methods Continuous electrocardiographic recording was performed during (32 minutes) and after (two hours) successive use of restraint and air-jet stress in 10 rats, whereas five rats serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…We found that immobilization stress could excite cardiac sympathetic activity and inhibit cardiac vagal activity. These results are consistent with previous studies that used other stress [20]. In recent decades, cardiac autonomic modulation has been a topical strategy in the prevention and treatment of heart diseases [21].…”
Section: Discussionsupporting
confidence: 92%
“…We found that immobilization stress could excite cardiac sympathetic activity and inhibit cardiac vagal activity. These results are consistent with previous studies that used other stress [20]. In recent decades, cardiac autonomic modulation has been a topical strategy in the prevention and treatment of heart diseases [21].…”
Section: Discussionsupporting
confidence: 92%
“…Emotional arousal induced sleep disorders may be mediated through increased sympathetic activation [84]. In the rat model, an increase in sympathetic nervous system index has been documented [85]. Activation of noradrenergic neurons and sympatho-adrenal axis by anxiety leads to increased secretion of epinephrine and norepinephrine, neurotransmitters which stimulate reticular activating system, and result in increased wakefulness.…”
Section: Occupational Stress-related Sleep Disorders In Frontline Hea...mentioning
confidence: 99%
“…A considerable amount of evidence suggests that the endothelin system is also implicated in autonomic responses during emotional stress. In rats, acute psychosocial stress increases plasma endothelin levels [ 52 ] and lowers vagal activity [ 53 ]. Remarkably, similar findings were reported in response to acute emotional excitement in healthy subjects and in patients with previous myocardial infarction [ 54 ].…”
Section: Acute Emotional Stress and Arrhythmogenesis During Myocardia...mentioning
confidence: 99%